Pharmacological evidence for CGRP uptake into perivascular capsaicin sensitive nerve terminals - Sams-Nielsen, Anette (2001)
1. Specific mechanisms, providing reuptake of cathecholamine and amino acid neurotransmitters (e.g. serotonin and glutamate) into cells of the central nervous system are well known, whereas neuronal uptake of neuropeptide transmitters have not previously been reported. 2. In the present study we present evidence for uptake of the 37 amino acid neuropeptide, calcitonin gene-related peptide (CGRP) into perivascular terminals of capsaicin sensitive nerve fibres, innervating the guinea-pig basilar artery. 3. Release of CGRP from perivascular nerve terminals was obtained by capsaicin-induced vanilloid receptor-stimulation and detected as CGRP receptor-mediated dilation of isolated segments of the guinea-pig basilar artery. 4. Following three repeated capsaicin challenges, CGRP-depleted segments were incubated with CGRP. This caused significant reappearance of capsaicin-induced vasodilatory responses. These responses were dependent on duration and concentration of the preceding CGRP incubation and were inhibited by the CGRP receptor antagonist, CGRP(8–37). 5. The CGRP-re-depletion was significantly reduced when CGRP(8–37) was present during the preceding CGRP incubation. Thus, presynaptic CGRP receptors are likely to be involved in neuronal CGRP uptake. 6. Incubating the artery segments with (125)I-CGRP allowed subsequent detection of capsaicin-induced (125)I-release. 7. Immunohistochemical experiments showed that only terminal CGRP is subject to capsaicin-induced depletion in vitro, whereas CGRP-immunoreactivity endures in the nerve fibres.